Kelsen H. Causality and Retribution / trans. from Engl. А. B. Didikin - А. B. Didikin (Омский научный вестник: Серия "Общество. История. Современность")
A translation of a paper by the Austrian philosopher and lawyer Hans Kelsen devoted to the conceptual understanding of the principle of causality in humanitarian knowledge is presented. The paper formulates and justifies the thesis that the origins of ideas about causality in nature should be found in ancient mythology and philosophy, where the key reference point for the perception of nature and society was the principle of retribution. On the basis of historical and philosophical reconstruction of the philosophical ideas of Heraclitus and Democritus Kelsen traces the evolution of the principle of causality to the present day, including the emergence of new theories in the field of quantum mechanics and mathematics